Pengaruh Pengalaman, Komitmen Profesi, Locus of Control dan Independensi Terhadap Perilaku Auditor dalam Situasi Konflik Audit - Amanda Intan Puspitasari; Muhammad Abdul Aris (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the influence of experience, professional commitment, locus of control and independence on the behavior of auditors in audit conflict situations . This study includes quantitative research with primary data types. Source data obtained from the filling of questionnaires. The population in this study are auditors who work at the public accounting firm (KAP) in Yogyakarta and Surakarta. Sampling technique performed in the study is to use convenience sampling, and the final result obtained a sample of 49 respondents. The results of the study can be concluded that the auditor's experience, professional commitment, and independence does not affect the behavior of auditors in audit conflict situations, while the locus of control affects the behavior of auditors in audit conflict situations.